Multiple Fano Resonances Based on Plasmonic Resonator System With End-Coupled Cavities for High-Performance Nanosensor - Chao Li; Shilei Li; Yilin Wang; Rongzhen Jiao; Lulu Wang; Li Yu (IEEE Photonics Journal)
A plasmonic resonator system composed of a metal-insulator-metal waveguide coupled with a disk and a ring cavity was proposed to produce double Fano resonances, which resulted from the coupling between the narrow discrete resonances of the ring cavity and the broad spectrum of the disk resonator. Based on the proposed structure, end-coupled cavities are added to form new coupled plasmonic resonator systems, which can support triple and quadruple Fano resonances, and the multiple Fano resonances can be tuned semi-independently by changing the parameters of the end-coupled cavities. These characteristics offer flexibility in the design of the highly integrated circuits. Also, the proposed structure can work as a highly efficient plasmonic nanosensor, which yields a sensitivity of ∼1100 nm/RIU and figure of merit (FOM) of ∼2.73 × 104. The proposed structure may have potential applications for nanosensing, slow light, and nonlinear devices in highly integrated devices.